Smart Card Madani: Solusi Berbasis Komunikasi Inovasi pada Pemerintahan Kota Pekanbaru, Riau - Toni Hartono; Febby Amelia Trisakti; Gista Aprilia (Jurnal Riset Komunikasi, 2021)
This article intends to discuss the existence of a new innovation initiated by the Pekanbaru City government, namely the Madani Smart Card product. The Madani Smart Card is one of the innovations of the Smart City program which is predicted to be a solution to urban community problems. This program has been proclaimed by the Pekanbaru City Government since 2017. The Madani Smart Card is an innovation of the Pekanbaru City government which is regulated in Law No. 23 of 2014 concerning Regional Government chapter XXI entitled Regional innovation, articles 386-390. The law states that local governments must carry out innovations that support regional development. This program is believed to be able to solve various urban problems such as public services, congestion, garbage accumulation, and citizen safety. This article is presented to answer problems that occur in the people of Pekanbaru City regarding the use of the Madani Smart Card. This study uses qualitative methods with interview data collection techniques, observation and documentation. The results of this study indicate that the Smart Card Madani program innovation helps the government in providing technology-based public services such as changing cash into electronic money, as a means of non-cash transactions at educational institutions, airports, and supermarkets, as well as a tool for attendance for City Government Civil Servants Pekanbaru.